Estudos hidráulicos e hidrológicos de amortecimentos de cheias do riacho Alagadiço, Fortaleza, CE - Sales, Raquel Jucá de Moraes (2011)
Recently, engineering researches which deal with urban drainage are proposing the use of computational tools in order to anticipate peak discharges of watersheds and the hydraulic behavior of drainage network system. The use of hydrological and hydraulic computer modeling ensures the minimization of errors in the engineering design process, as well as an increase in quality of the drainage planning work.Therefore, the actual study uses two well know drainage computer codes HEC-HMS and SWMM to design structures to decrease discharge peaks in a watershed situated in a critical area of Fortaleza with respect to floods.This watershed is located west of the city of Fortaleza and at drains the Alagadiço stream, which is also the name of the basin. Computer simulation were performed using return periods of 20, 50 e 100 year with and without the presence of dams using both HEC-HMS andSWMM.It was proposed three dams and they were simulated separately and altogether.Result of the simulation showed that the presence of only two dams, caused a significant decrease in flood peaks. According the HEC-HMS this reduction was 24%. According to SWMM, this reduction was 42%. This study is a contribution to the use of computer models in designing urban flood control structures.